Evaluation of intervention to address seasonal availability of fruits/vegetables and preferences/barriers for consumption by peri-urban and urban low-income men and women in Hanoi and Ibadan - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
Sample size: Hanoi: 96 (51women/48men); Ibadan: 97 (55women/42men); seasonality FGDs: Hanoi: 8 gender specific focus groups(GSFG) 96 participants (10-13 people); Ibadan: 4 gender GDFG with 10 people.